Recruitment and Retention of Football Players as Determinant of Nigeria Professional Football League Clubs’ Performance at National and Continental Competitions - Adekola, Ridwan Ademola; Okundare, Ayobami Alade (Journal of Physical Education and Sport Pedagogy, 2025)
Nigeria Premier Football League (NPFL) clubs have struggled to produce players capable of representing Nigeria at continental and international competitions. Most national team players across all levels are sourced from European clubs, highlighting the low competitiveness of the NPFL. This study examined how player recruitment and retention influence NPFL clubs’ performance in national and continental tournaments. A mixed-method research design was adopted, with a sample of 420 football stakeholders. Instruments used included Players’ Recruitment and Players’ Retention questionnaires. Findings showed that recruitment and retention had no significant impact on club performance at either national or continental levels (Recruitment: R = 0.077, R² = 0.006, F = 0.018, p 0.05; Retention: R = 0.426, R² = 0.181, F = 0.665, p 0.05). The study concluded that these factors alone do not significantly influence performance. Instead, a combination of elements such as funding, financial management, coaching quality, and administrative competence play a more critical role. It is recommended that football stakeholders urgently integrate key administrative factors to enhance the NPFL’s performance and elevate its status both nationally and continentally.